The “Grenoble phenomenon” through the prism of an innovative company - Régis Boulat (Revue de Géographie Alpine)
This portrait of the Jamet company, manufacture of sports equipment and leisure founded in Grenoble in 1929 by the young ski champion Andre Jamet emphasizes the emergence of new sport practices, the transformation of land uses and the development of new markets illustrating the appearance of a new industrial sector in the Alps.